Indication of recent warming process at the intermediate level in the Tyrrhenian Sea from SOOP XBT measurements - RIBOTTI, A.; SORGENTE, R.; OLITA, A.; ORILIA, F.; BORGHINI, M.; RESEGHETTI, F. (Mediterranean Marine Science, 2016)
The Tyrrhenian Sea is a sub-basin of the western Mediterranean crossed by intermediate and deep waters from the eastern basin. Across this sub-basin, temperature profiles of the water column from expendable bathythermographs (XBT) have been acquired for sixteen years along transects realized thanks to the use of commercial vessels. Since 1999 an increase of temperature has been observed at intermediate depths even if interspersed with periods of decrease. This increase involves deeper and deeper depths along the years then involving the whole sub-basin in the range 200-800 m in September 2014 when largest anomalies over the whole period are found. The paper shows evidences of this rapid heating, giving insights into the origin and the diffusion of the warmer intermediate waters then showing its evolution in years and its relationship with the Eastern Mediterranean Transient.